2015
DOI: 10.1016/j.bbadis.2014.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol and diabetes: from animal to human studies

Abstract: Diabetes mellitus is a serious disease affecting about 5% of people worldwide. Diabetes is characterized by hyperglycemia and impairment in insulin secretion and/or action. Moreover, diabetes is associated with metabolic abnormalities and serious complications. Resveratrol is a natural, biologically active polyphenol present in different plant species and known to have numerous health-promoting effects in both animals and humans. Anti-diabetic action of resveratrol has been extensively studied in animal models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
220
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 309 publications
(224 citation statements)
references
References 104 publications
4
220
0
Order By: Relevance
“…An array of additional molecules with anti-oxidant properties improve several circulating markers of T2D such as fasting blood glucose, HbA1c, insulin, and lipid (LDL and triglycerides) levels (Azadmehr et al 2014, Szkudelski & Szkudelska 2015. Among them resveratrol was shown to protect against ER stress-driven cell dysfunction in the context of obesity-related disorders and diabetes (Andrade et al 2014.…”
Section: Existing Treatments Of T2d That Reduce Er Stressmentioning
confidence: 99%
“…An array of additional molecules with anti-oxidant properties improve several circulating markers of T2D such as fasting blood glucose, HbA1c, insulin, and lipid (LDL and triglycerides) levels (Azadmehr et al 2014, Szkudelski & Szkudelska 2015. Among them resveratrol was shown to protect against ER stress-driven cell dysfunction in the context of obesity-related disorders and diabetes (Andrade et al 2014.…”
Section: Existing Treatments Of T2d That Reduce Er Stressmentioning
confidence: 99%
“…Resveratrol is able to target cytomembranes, intracellular receptors, signaling molecules, enzymes, oxidative system, DNA repair system and transcription factors (12). Cellular signal transduction function is able to convert stimulation into a signal, and this process frequently involves a series of biochemical reactions (13). Resveratrol regulates a series of signal transduction pathways, such as the SIRT1 and NF-κB signaling pathways (14).…”
Section: Introductionmentioning
confidence: 99%
“…Resveratrol (RSV), a natural polyphenol found in grapes and red wine (10), may potentially attenuate hepatic steatosis and reduce the risk of patients developing T2DM (11). It has previously been demonstrated that RSV activates Sirtuin type 1 (SIRT1) to inhibit the development of T2DM (12). SIRT1 is a nuclear NAD + -dependent class III histone deacetylase that may regulate cell aging, life span and energy metabolism (13) by engaging in the reciprocal co-regulation of different binding partners (14).…”
Section: Introductionmentioning
confidence: 99%